Assessment of food safety and food handling knowledge of Catanduanes freshwater shrimp fisherfolk - Candelaria, Jude Steven A.; Pagulayan, Jin Mark GD (Quezon City University of the Philippines Diliman, 2024)
The economical importance of the prawn industry in the Philippines highlights the need to address possible risks and challenges to prevent or minimize occurrence of foodborne illnesses and contamination. To provide information on prawn farming, this study investigated the food safety knowledge, attitudes, and practices (KAP) of Catanduanes prawn fisherfolks (n=30) through a survey and observation of actual food safety practices. Results showed that the participants had a good food safety knowledge (82.00 ± 12.88%) and food safety attitude (93.67 ± 4.04%) based on their mean scores related to personal hygiene, contamination, social responsibility, and cleaning and sanitation. Despite having good self-reported food safety practices (74.67 ± 8.19%), it was in contrast with observed food safety practices based on the obtained score of 50.00 ± 7.56% in the areas of contamination, cleaning and sanitation, and some concepts in personal hygiene. The study showed how food safety knowledge and attitude does not always reflect actual practice of food safety. This suggests that local authorities should become more strict in ensuring adherence and compliance to the Good Aquacultural Practices (GAqP) standards by encouraging the prawn farmers in Catanduanes, especially the farm owners, to adopt GAqP certification. The results from the study may be used as a basis for future studies regarding the current challenges and problems regarding prawn farming and aquaculture in the country.
In partial fulfillment for the Degree of Bachelor of Science in Food Science and Nutrition
Thesis
Keywords: Food handling -- Philippines; Food safety; Aquaculture; Prawn fisheries; Knowledge, attitudes, and practices (KAP).; Fishery products